Dzieło muzyczne jako przestrzeń doświadczania emocji na przykładzie własnej kompozycji "Punctum" na orkiestrę smyczkową - Kwiecień-Długosz, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject matter of this article titled is the eponymous musical composition and its relationships with two fields of art therapy: phototherapy and music therapy. The author reflects on the ways in which disease and fears influence creativity, on the significance of the non-verbal language of art for experiencing emotions, on the potential of photography for uncovering hidden subconscious content, and on the musical work as a space for non-verbal expression of messages. The article contains a description of the creative process (divided into the pre-production, realization, and performance preparation stages) and an analysis of the "Punctum" composition.
Keywords: dzieło muzyczne; autoterapia; fotografioterapia; muzykoterapia; emocje; emotions; musical work; self-therapy; phototherapy; music therapy